GAMBARAN PENGETAHUAN IBU TENTANG PIJAT BAYI DI RUMAH BERSALIN AN-NUUR KABUPATEN KARANGANYAR - Melawati Artika Wulansari (OVUM : Journal of Midwifery and Health Sciences, 2021)
Background : Baby massage is the oldest and most popular touch therapy known to humans and has been passed down from generation to generation. Touch and massage of the baby after birth can provide assurance of continuous body contact that can maintain a feeling of security in the baby. The purpose of the study was to describe the mother's knowledge about infant massage at the An-Nuur Maternity Home, Karanganyar. Research Methods: the type of research used is descriptive quantitative. The sample is a mother who massages her baby at the An-Nuur Karanganyar maternity home. Sampling technique Acidal sampling obtained 61 respondents. The instrument used is a questionnaire. Univariate data analysis with frequency distribution. The results of the study: to 61 mothers at the An-Nuur Maternity Home, Karanganyar, 9 respondents (14.7%) had good knowledge, 42 respondents (68.8%). %).Conclusion: that the mother's knowledge about baby massage at the An-Nuur Maternity Hospital Karanganyar is mostly in the sufficient categor